Effects of affective variables and willingness to communicate on students’ English-speaking performance in Thailand - Budi Waluyo; Rahmah Bakoko (Universitas Syiah Kuala, 2022)
Recently, Willingness to Communicate (WTC) has been explored and proposed to be one of the key concepts for identifying when one decides to initiate communication in the target language. The attention, nonetheless, has been concentrated on how WTC interacts with other learners’ variables. This study, on the other hand, intends to offer empirical evidence on the direct roles of affective variables (self-confidence, anxiety, motivation, and grit) and WTC variables (WTC inside the classroom, WTC outside the classroom, and WTC in a digital setting) in Thai students’ English-speaking performance. The data were obtained from 35 undergraduate students (17.1% males; 82.9% females) using a survey questionnaire. Then, a speaking test was taken from an English Communication Skills course and was analysed using correlation and hierarchical regression. The results disclosed positive correlations among self-confidence, motivation, grit, WTC in a digital setting, WTC inside the classroom, WTC outside the classroom, and speaking performance, and negative correlations among self-confidence, anxiety, and grit. However, motivation was the only significant predictor of speaking performance. The findings offer some implications for English teachers in improving students’ English-speaking performance.